Slawter - Shan, Darren (London : Harper Collins, 2006)
While on a horror movie set with his Uncle Dervish, Grubbs Grady realizes that his battle with the evil demon master Lord Loss may be about to resume.
HarperCollins Children's Books.
Keywords: Demonology -- Fiction; Magic -- Fiction; Horror stories; Motion pictures -- Production and direction -- Fiction